The Strategic Role of Islamic Education in Responding to Social Changes in Coastal Communities: an Interdisciplinary Literature Review - Danang Eko Saputro (Global Journal of Islamic Education, 2026)
Coastal communities face structural challenges such as economic instability, limited access to education, low levels of religious literacy, cultural vulnerability, weak social governance, early marriage practices, marginalization, and environmental degradation. This complexity hampers their ability to adapt to social change and calls for more responsive educational interventions. This study aims to analyze the role of Islamic education in addressing these issues and to formulate an integrative conceptual model that combines Islamic values, coastal social dynamics, and empowerment approaches. Using a literature study with a thematic approach, this research examines academic literature, Islamic education theories, and coastal social studies. The findings indicate that Islamic education holds strategic potential through strengthening contextual religious literacy, internalizing maqāṣid al-sharī‘ah, developing adaptive curricula, promoting cultural da‘wah, facilitating social mediation, preventing early marriage, and fostering ecological literacy based on the concept of humans as khalīfah fil arḍ. The resulting integrative model emphasizes the importance of value internalization, social needs mapping, and multisectoral collaboration. This study contributes to expanding a more transformative, contextual, and locally grounded paradigm of Islamic education. In conclusion, Islamic education has the potential to serve as an agent of social transformation in coastal communities, although it still requires strengthened curriculum relevance, improved networking, and enhanced practical implementation to be more effective and sustainable.